Irrigation systems as common-pool resources - Giangiacomo Bravo; Beatrice Marelli (Revue de Géographie Alpine)
Common-pool resources are natural or man-made resources shared among different users, a condition that produces a competition for their utilization leading often (although not necessarily) to their degradation or even to their destruction. This paper shortly discusses the "theory of the commons", as developed in the last 20 years by Elinor Ostrom and her colleagues, and illustrates it by mean of case studies regarding a number of irrigation systems in Northern Italy (Lombardy and Aosta Valley). We show that that different social mechanisms, like the shared values e the social network existing inside the community of users, play a significant role in influencing the outcomes of the institutional schemes for the commons management.